Analysis of Teenage Students' Moral Through Physical Education - Ismail, Ghulam Zaky; Ridwan, Mochamad; Ockta, Yovhandra (STKIP Singkawang, 2024)
The challenges faced by young people today in shaping their morality from adolescence can be identified through Physical Education (PE) learning. PE plays a significant role in shaping the morals and character of adolescent students. It goes beyond focusing solely on knowledge and psychomotor skills, incorporating essential moral aspects. By promoting discipline, fostering collaboration, and instilling a sense of responsibility, PE helps in molding well-rounded individuals.The objective of this study was to identify the moral values of adolescent students through PE learning. A descriptive research method with a quantitative approach was employed. Data collection was carried out using a Likert scale questionnaire. The sample consisted of 64 junior high school students selected through random sampling techniques. This research utilized three indicators to describe the moral values of adolescent students: discipline, collaboration, and responsibility. The classification for determining good morals was based on standard categories of excellent, good, fair, poor, and very poor. The results showed that the moral values of adolescent students were as follows: 20% of students were classified as excellent, 78% as good, and 2% as fair, with no students falling into the poor or very poor categories. These findings indicate that PE learning significantly contributes to the moral development of adolescent students. Consequently, it can be concluded that PE learning is integral to shaping the morals of adolescent students, playing a crucial role in their overall development and character building. The positive impact observed underscores the importance of incorporating moral education within the PE curriculum to nurture disciplined, collaborative, and responsible individuals.